1999
DOI: 10.1007/s11746-999-0009-3
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical carbon dioxide extraction of lipids from Pythium irregulare

Abstract: Lipids that contain polyunsaturated fatty acids (PUFA) have therapeutic value. PUFA, however, degrade in high-temperature, oxygen-rich conditions typical of conventional hot solvent-extraction and distillation methods. Supercritical CO 2 extraction was chosen as an alternative method to recover these valuable compounds from the lower fungus, Pythium irregulare. Freeze-dried biomass was subjected to an aqueous phase and placed into a flow-through extraction apparatus. Extraction of oil from this biomass showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 31 publications
0
16
0
1
Order By: Relevance
“…After heating to 95°C for 30 min, the sample was immediately mixed with n-hexane for 5 min, and the LEY was 77% (Balasubramanian et al, 2011). The SCF method has also been applied to lipid extraction from the wet cell mass, but was not applicable to high moisture content feed (Walker et al, 1999). Mixing of high moisture cell mass with a scCO 2 -soluble surfactant enabled better extraction of the lipids.…”
Section: Optimization Of the Lipid Extraction Processmentioning
confidence: 99%
“…After heating to 95°C for 30 min, the sample was immediately mixed with n-hexane for 5 min, and the LEY was 77% (Balasubramanian et al, 2011). The SCF method has also been applied to lipid extraction from the wet cell mass, but was not applicable to high moisture content feed (Walker et al, 1999). Mixing of high moisture cell mass with a scCO 2 -soluble surfactant enabled better extraction of the lipids.…”
Section: Optimization Of the Lipid Extraction Processmentioning
confidence: 99%
“…It was found that supercritical CO 2 extraction at 30 MPa and 50°C yielded greater than 110% of the c-linolenic acid that was obtained by chemical extraction. Walker et al (1999) also extracted x-3 fatty acids using SFE from P.…”
Section: Extraction Of Hops Hopsmentioning
confidence: 99%
“…L'extraction peut également être optimisée par une intensification des conditions de température et de pression permettant ainsi d'augmenter le pouvoir de solvatation du solvant mis en jeu (Walker et al, 1999 ;Chen et al, 2011).…”
Section: L'extraction Par Solvant Organiqueunclassified